'Kite-tail' fascia lata strips technique: frontalis suspension using a non-endoscopic minimally invasive single-thigh incision approach. Issue 4 (17th November 2011) - Evereklioglu, Cem
Abstract : Aim: To introduce 'kite-tail' strips or a 'multiple Z-plasty' technique on an autogenous fascia lata graft without a stripper to correct severe blepharoptosis by frontalis suspension and to evaluate its effectiveness on surgical outcome. Methods: 26 eyelids of 18 patients (seven women, 11 men; 10 unilateral, eight bilateral) underwent this procedure. Only a small skin incision was made on the leg measuring 2 cm. A final of 3.5×0.6 cm or 5×1 cm fascia lata strip was obtained according to the ptosis laterality. The obtained fascia lata graft was then dissected by a described stripping technique for a final of one or two fascia lata strips approximately 12.5 cm×2 mm long. Functional and cosmetic results were evaluated and the advantages of this technique were stressed. Results: Mean age was 26.0 years (range 3–64) with a mean follow-up period of 28.8 months (range 6–52). All cases achieved good to excellent final lid positions and adequate cosmetic results with no postoperative early (haemorrhage, wound infection) or late (contour abnormality, overcorrection, muscle herniation, recurrence) complications. Conclusions: This is an easily mastered, simple, safe and efficient alternative technique that offers various benefits over conventional approaches. It avoids extended blunt dissections and has fewer postoperative leg complaints with less haemorrhage–haematoma formation or muscle prolapsus. It is useful at any age, especially in small children who already have a limited amount of delicate fascia lata and may be preferred when a fasciotome or videoendoscope is not available or fails to harvest sufficient material of fascia lata.